Analisis Kesalahan Pembentukan Kata pada Berita Daring Kompasiana.Com yang Berjudul “Pakuwon Mall Surabaya Inovasi Green Building untuk Lingkungan yang Berkelanjutan” - Hilda Nurhidayah; Vincentius Marvellio P.H; Rizqy Nasrullah Cahyanto; Taswirul Afkar (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to determine (1) spelling and writing errors; (2) grammatical errors; (3) punctuation errors; and (4) inconsistent use of terms in Kompasiana's online news entitled "Pakuwon Mall Surabaya Green Building Innovation for a Sustainable Environment". This study uses a qualitative descriptive method with documentation methods and literature studies or literature reviews and observations as data collection techniques. Based on the analysis carried out, there are several related errors: (1) spelling errors including typos and use of prepositions; (2) grammatical errors including incorrect use of sentence subjects and use of phrases; (3) punctuation errors including the lack of use of commas in several sentences; and (4) inconsistent use of terms including the use of foreign languages ​​that are not accompanied by their meanings.